Characterization of the complete chloroplast genome of Clerodendrum bungei Steud. (Lamiaceae). Issue 7 (3rd July 2021) - Wang, Yan; Wang, Hanping; Wang, Jinpei; Li, Peng; Zhou, Xujiang; Zhang, Wanjing; Zhou, Baozhen; Li, Chenxi; Yue, Zhiyong
Abstract: Clerodendrum bungei Steud. is one kind of traditional medical herb which can be used for airway hyperreactivity treatment. In this study, the complete chloroplast genome sequence of C. bungei was assembled. Its complete circular chloroplast DNA length was 151, 680 bp. The genome was made up of a large single-copy region of 83, 189 bp, a small single-copy region of 17, 311 bp, and a pair of inverted repeat regions of 25, 590 bp. The genome totally encoded 130 genes, containing 85 protein-coding genes, 37 tRNA genes, and eight rRNA genes. The phylogenetic analysis indicates that C. bungei belongs to the Lamiaceae family.